(untitled) (Terr@ Plural, 2021)
The class Tentaculitoidea is an extinct group composed of small carbonate coniform-shaped invertebrates, distributed from Ordovician to Devonian. This group is more often recorded to the North Hemisphere, being less recorded to South Hemisphere deposits. This study aims (i) to analyze the species found in Brazilian Devonian outcrops, in addition (ii) to investigate their paleogeographic and stratigraphic distribution. The analyzed samples, which come from Paraná, Amazonas, and Parnaíba basins, are hosted in 9 Brazilian Research Centers. It was diagnosed 12 species of tentaculitoids: Tentaculites crotalinus, Tentaculites jaculus, Tentaculites kozlowskii, Tentaculites paranaensis, Tentaculites eldredgianus, Tentaculites trombetensis, Tentaculites stubeli, Tentaculites oseryi, Uniconus ciguelii, Homoctenus katzerii, Styliolina langenii, and Styliolina clavulus. The species from Paraná Basin are different from those recorded in Amazonas and Parnaíba basins, all present distinct stratigraphic ranges (Pragian to Givetian in Paraná Basin and Eifelian to Givetian in Amazonas and Parnaíba basins).